Puromycin-Peptide Bond Formation with Reticulocyte Initiation Factors M(1) and M(2) - Shafritz, David A. (1971)
The ability to form a “peptide” bond between various forms of Met-tRNA or Phe-tRNA and puromycin has been studied in the reticulocyte cell-free system. When Met-tRNA(F), fMet-tRNA(F), or N-acetylPhe-tRNA are used as substrate at low Mg(++) concentration (3 mM), reticulocyte initiation factors M(1) and M(2) (M(2A) + M(2B)) are required for puromycin-peptide synthesis. In contrast to bacterial systems, this reaction is also stimulated by the elongation factor T(1). When Met-tRNA(M) or Phe-tRNA is used as substrate, there is no M-factor requirement for the puromycin reaction; T(1) is absolutely required, and the reaction is stimulated by T(2). These studies indicate that reticulocyte factors M(1) and M(2) may function in part by placing the initiator tRNA into the P site. The detailed mechanism for mammalian initiation, however, may be more complex than that for bacterial systems.